2018
DOI: 10.1101/272427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The thalamus regulates retinoic acid signaling and development of parvalbumin interneurons in postnatal mouse prefrontal cortex

Abstract: GABAergic inhibitory neurons in the prefrontal cortex (PFC) play a crucial role in higher cognitive functions. Although disruption of their normal development is linked to a number of psychiatric disorders, cellular and molecular mechanisms underlying the normal development of these neurons are poorly understood. Here we found that during postnatal mouse development, Cyp26b1, a gene encoding a retinoic acid-degrading enzyme, is strongly expressed in the PFC and that medial ganglionic eminence (MGE)- show that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
2
5
0
Order By: Relevance
“…18a). Consistent with previous findings in humans 21 and mice 24 , whole-mount and serial tissue section in situ hybridization revealed that Cyp26b1 is upregulated in the prospective motor cortex (MOs and MOp) and anterior insula compared to the mPFC and OFC, defined by high expression of Cbln2, and SSp, defined by Rorb (Fig. 5a, b, Extended Data Fig.…”
Section: Articlesupporting
confidence: 91%
See 3 more Smart Citations
“…18a). Consistent with previous findings in humans 21 and mice 24 , whole-mount and serial tissue section in situ hybridization revealed that Cyp26b1 is upregulated in the prospective motor cortex (MOs and MOp) and anterior insula compared to the mPFC and OFC, defined by high expression of Cbln2, and SSp, defined by Rorb (Fig. 5a, b, Extended Data Fig.…”
Section: Articlesupporting
confidence: 91%
“…RA signalling has previously been shown to be involved in the regulation of proliferation, cell cycle timing and cortical laminar development [22][23][24] , which could underlie our findings. Thus, we assessed whether the constitutive deletion of Rarb and Rxrg leads to changes in cortical size and laminar organization.…”
Section: Articlesupporting
confidence: 68%
See 2 more Smart Citations
“…Anxiety symptoms are common in schizophrenia patients [40,41]. Cyp26b1 is is expressed in parvalbumin-positive interneurons [42]. Most interestingly, knockdown Cyp26b1 in the nucleus accumbens shell decreased anxiety-like behavior [43].…”
Section: Discussionmentioning
confidence: 99%